Penerapan Pembelajaran Matematika Realistik Pada Penjumlahan Pecahan Dapat Meningkatkan Hasil Belajar Siswa Kelas V SDN 28 Kota Parepare - Yonathan Saba' Pasinggi; Rita Thuken (Publikasi Pendidikan, 2019)
This study aims to determine the use of a PMRI (Realistic Mathematics Education Indonesia) on mathematics learning can enhance students' understanding of the sum of fractions in grade V SDN 28 Kota Parepare. This study uses kualitiatif approach, this type of research is action research class that is located in SDN 28 Kota Parepare. Site selection based on the consideration of researchers looked at the implementation of a realistic approach to learning mathematics in primary schools has not been applied. TOD study procedures that (1) Perrencanaan, (2) Implementation, (3) observation, (4) reflection. Data collection techniques used in this study include (1) observation, (2) documentation, (3) interviews, (4) tests. Data analysis is an effort to improve student learning outcomes with the implementation of realistic mathematics approach. The results on initial tests showed that students' ability to understand the subject matter is still lacking in that category, after learning showed a significant increase with the evaluation results on the cycle I was on a qualifying well (B), continued research on the cycle II because researchers are not satisfied with the results obtained in cycle I, the evaluation results on the second cycle showed a significant increase in the category of very good results. This shows that the application of realistic mathematics approach can improve learning outcomes of students in the SDN 28 Kota Parepare.